Information : Documents of Contemporary Art. - Cook, Sarah; Bridle, James; Dietz, Steve; Frohne, Ursula; Fuller, Matthew; Gallo, Francesca; Hudek, Antony; Kac, Eduardo; Kittler, Friedrich; Kroker, Arthur and Marilouise; Lash, Scott; Ludovico, Alessandro; et al. (London : Whitechapel Gallery, 2016)
Askevold, David ; Baxter, Iain ; Bleus, Guy ; Bunting, Heath ; CAMP ; Clarke, Ami ; Dickinson ; Rod ; Haacke, Hans ; Harwood, Graham ;Holzer, Jenny ; Kosuth, Joseph ; Kozlov, Christine ; Lambert, Steve ; Laric, Oliver ; Levine, Les ; Mattes, Eva & Franco ; Moholy-Nagy, Laszlo ; Muntadas ; Muratoglu, Erhan ; Raqs media Collective ; Scourti, Erica ; Stelarc ; Thomson & Craighead ; Vander zaag, Elizabeth ; Waller, Angie ; Willats, Stephen ; The Yes men ; Young-Hae, Chang ; Heavy Industries
boek